74.9k views
5 votes
Enter the correct answer in the box.

Factor the expression x2 + 4x − 12.

User Anayarojo
by
5.5k points

2 Answers

0 votes

Answer:

(x-2)(x+6)=0; x=2, x=6

Explanation:

Assuming you meant x^2

Easy factoring here.

x^2+4x-12=0

What multiples to get -12 and adds to get +4

-2 and 6

(x-2)(x+6)=0; or x=2, x=-6

User Shamal
by
4.7k points
2 votes

Answer:

(x + 6)(x - 2)

Explanation:

Find factors of x² and -12 that, when FOILed, would give you 4x in the middle.

In this case, use the factor 6 & -2:

x² + 4x - 12

x 6

x - 2

(x + 6)(x - 2) is your answer.

Check. Use the FOIL method:

FOIL =

First, Outside, Inside, Last

(x)(x) = x²

(x)(-2) = -2x

(6)(x) = 6x

(6)(-2) = -12

Combine like terms:

x² (-2x + 6x) - 12 = x² + 4x - 12

~

User Fernando Barbeiro
by
5.1k points